The awareness level on financing long term care cost among rural-urban and marital status in Malaysia - Yusuf M.M.; Hamdy M.S.; Ruslan N.A.; Basah M.Y.A. (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA